ETIOLOGY, PATHOGENESIS AND MORPHOLOGY OF BILIARY ATRESIA - O. E. Iryshkin; I. M. Ilyinsky; O. M. Tsirulnikova; S. V. Gautier (Вестник трансплантологии и искусственных органов)
Biliary atresia is an inflammatory fibrosing process, which invades both extrahepatic and intrahepatic bile ducts. There are two forms of biliary atresia: embryonic form, associated with another visceral malformations, and perinatal form, which is an isolated disease. Biliary atresia is a heterogeinc disease which may appear as a result of different etiological factors, the most important of them are genetics, viral infection, vascular factors, toxins and disregulation of immune system. The characteristic morphological features of biliaryatresia are: intracellular and ductular cholestasis, ductular proliferation, giant cell transformation, portal and perilobular oedema and/or fibrosis. As the patalogical process progresses, ductopenia appears, and fibrosis turns to cirrhosis. Embryonic form mophologically manifests with ductal plate malformation is, what is an important diagnostic criterion. Pro- gnosis of biliary atresia depends on form of disease, age of patient and type of surgical operation. Today surgical treatment includes two steps: palliative portoenterostomia, performed in neonatal period and further liver trans- plantation. However liver transplantation is more preferable as first and single-step treatment.